Effect of easy five training programme on technical and tactical performance in Malaysian junior tennis players / Mohamad Rahizam Abdul Rahim - Mohamad Rahizam , Abdul Rahim (2018)
An athlete‟s success or optimal performance during competition is the ultimate goal of any coaches. This study is to explore the effects of Easy Five training programme on technical and tactical performance of Malaysian male junior tennis players. The motive of this study is to seek out a realistic and feasible solution in order to enhance the performance of Malaysian junior tennis players. It involved a discussion of the theoretical issues raised especially on the effectiveness of Easy Five training programme as well as its relation with previous research. A total of thirty junior tennis players (n=30) were selected in this study and were divided into Experimental and Control groups with each group consists of fifteen participants (n=15). All participants were tested on their performance variables namely the Groundstroke Depth, Groundstroke Accuracy, Volley Depth, Serve, Agility and International Tennis Number (ITN) total score. The Experimental group was engaged into the Easy Five training programme and Control group went through tennis match play for 8 weeks. These methods correlate with the objectives of this study which focuses on the technical and tactical performance of all the participants and investigating the effects of an Easy Five on the performance of the Malaysia junior tennis players. A mixed between-within subject analysis known as split-plot ANOVA (SPANOVA) was used to test the research questions. The pairwise comparison within group test of pre-test and post-test results indicated that there was a statistical significant difference in the performance of Experimental group in Groundstroke Depth (p = 0.001), Groundstroke Accuracy (p = 0.001), Volley Depth (p = 0.001), Serve (p = 0.01), Agility (p = 0.001) and International Tennis Number (ITN) total score (p = 0.001). The results proved that participants from Experimental group showed an improvement in all of the performance variables and also validate the positive effect of Easy Five training programme. Control group showed a slight improvement in agility performance with (p = 0.01). Results from statistical analysis also indicated that there are statistical significant difference between the two groups after 8 weeks treatment in Groundstroke Depth (F1,28 = 12.59; p = 0.01), Groundstroke Accuracy (F1,28 = 15.24; p = 0.01), Volley Depth (F1,28 = 29.55; p = 0.001) and ITN total score (F1,28 = 61.33; p = 0.001) but indicated no significant difference in agility (F1,28 = 1.53; p = 0.23) and serve (F1,28 = 1.14; p = 0.29) performance which dictate the optimistic effect of intervention training programme engaged in this study. The findings revealed that the Easy Five which reflects the game situations training approach is a viable method in formulating a training programme as it shows positive effects on the performance and provides significant recommendations to coaches and players about designing an effective training programme.